Islam and Identity Politics In The 2019 Presidential Election (From The Perspective of Structuration Theory) - Al Amin, Mukayat; Marijan, Kacung; Asfar, Muhammad (Sahafa Journal of Islamic Communication, 2024)
We already know that the 2019 presidential election contestation is a very harsh contestation between two pairs of presidential candidates, namely Jokowi and Prabowo. The severity of the contestation is feared to trigger horizontal conflicts and people divisions which causing at least 8 people to die in the election results protest on May 21-22, 2019 in Jakarta. The severity of the contestation is one of the things because the 2019 presidential election involves identity political practices. Therefore this research intends to analyze how much the role of agents and structures in influencing the independence of political choices of voters in each Identity. In the process of analysis this research uses Anthony Giddens' Theory of Structuralization. Departing from Anthony Giddens' theory of structure, this research seeks to explore how significant the influence of agents and structures in influencing the independence of political choices of voters. This research uses qualitative research methods with a critical empirical approach. In this study, it has been found that in influencing the independence of political choices, agent voters and structures are supported by two things, namely alocative and authoritative resources, but in this study there is a finding that to influence the nature of the independence of political choices, voters is not enough only with alocative and authoritative resources, but we find that there are logistical and historical resources that play a significant role in influencing the independence of the political choices of each voters.   Keyword: Identity Politics, Historical, Logistics.